Damsels and Divas : European Stardom in Silent Hollywood - Frymus, Agata, 1989- (Book collections on Project MUSE., 2020)
"Damsels and Divas investigates the meanings of Europeanness in Hollywood during the 1920s by charting professional trajectories of three movie stars: Pola Negri, Vilma Bánky and Jetta Goudal. It combines the investigation of American fan magazines with the analysis of studio documents, and the examination of the narratives of their films, to develop a thorough understanding of the ways in which Negri, Bánky and Goudal were understood within the realm of their contemporary American culture. This discussion places their star personae in the context of whiteness, femininity and Americanization. Every age has its heroines, and they reveal a lot about prevailing attitudes towards women in their respective eras. In the United States, where the stories of rags-to-riches were especially potent, stars could offer models of successful cultural integration"--